A Study on core competence management - Lee, Han-Kyoung (KDI School, 1998)
The major objective of this study is to understand the concept and methodology of core competence management. The survival and growth of a company depends on competitive advantage, and effective core competence management. By examining the related literature and analyzing of the case study of Canon, I explain the importance of core competence management as a source of a firm’s competitive advantage and future growth potential. Core competence gives companies significant meaning. The company that has a systematically structured core competence does not experience difficulties despite the changing environment. Core competence offers long-term and differentiated advantage to companies. In other words, core competence provides companies with the source of true competitiveness. That is why so many companies are investing their resources in strengthening their core competence. Korean companies had a tendency to focus on new markets or the attractiveness of an industry rather than on the relatedness with the existing business. Unrelated diversification could be successful to some extent because the first mover in the new market could enjoy some advantage when the industry is in the growing stage and competition is restricted. However, diversification will not be successful if a company pursued it only because of the attractiveness of the market at the neglect of systematic core competence management.
Thesis(Master) --KDI School:Master of Strategy & International Management,1998